THE ROLE AND IMPORTANCE OF SOCIAL AND POLITICAL INSTITUTIONS IN RAISING THE SENSE OF SPIRITUAL TOLERANCE AMONG YOUNG PEOPLE - Aripov Alisher Abdumalikovich (Journals Park Publishing, 2022)
This article talks about the role and importance of social and political institutions in raising the moral tolerance of youth.
Keywords: tolerance, spirituality, enlightenment, culture, personality, society.